Physical Aging of Zr65Cu17.5Ni10Al7.5 Glassy Alloy. (August 2019) - Aji, Daisman P.B.; Triyono,; Mujalis, Yusep
Abstract: Physical aging of Zr65 Cu17.5 Ni10 Al7.5 glassy alloy has been studied after holding its samples with variation of time and temperature of annealing. The results showed that the enthalpy and entropy decreased with time according to a non-exponential kinetics. The Differential Scanning Calorimetry (DSC) heating scan after annealing was analyzed using Tool-Narayanaswamy-Moynihan (TNM) model. The analysis showed that a set of parameters that fitted the heating scan data for one annealing time did not fit the heating scan data for another annealing time. This is explained due to approximations used in the model and the effect of Johari-Goldstein (JG) relaxation to the physical aging.